Improving Brand Love through Emotional, Loyalty, and Susceptibility to Normative Influence - Laksana, Muhammad Hafid; Kuswati, Rini (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this research is to analyze the effect of emotional brand attachment and brand loyalty on brand love as mediated by susceptibility to normative influence. The population of this study is Indonesia's Apple product consumers, and a sample of 150 respondents was gathered. The sample selection used a non-probability sampling method, specifically using purposive sampling. Smart PLS 3.0 software was utilized for data analysis. The analytical results of this study show that brand loyalty has a significant effect on brand love, brand loyalty has a significant effect on susceptibility to normative influence, emotional brand attachment has a significant effect on brand love, emotional brand attachment has a significant effect on susceptibility to normative influence, and susceptibility to normative influence has a significant effect on brand love. Eventually, susceptibility to normative influence fully mediates the effect of both brand loyalty on brand love and emotional brand attachment on brand love. The integration of these concepts is anticipated to enhance the understanding of the relationship between brand love. Future research should delve into the exploration of susceptibility to normative influence in this context, with a focus on comprehending its more profound effects on brand love. As a suggestion for further research, additional exploration can be conducted regarding other factors that may mediate the relationship between these variables, as well as cross-brand research to broaden the generalizability of the research results.